2020
DOI: 10.21203/rs.3.rs-90892/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rhabdomyolysis is Associated with Hospital Mortality in Patients with COVID-19

Abstract: Purpose: To evaluate the clinical features and outcomes of rhabdomyolysis (RM) in patients with COVID-19. Method: A single center retrospective cohort study of 1,014 consecutive hospitalized patients with confirmed COVID-19 at the Huoshenshan hospital in Wuhan, China, between February 17 and April 12, 2020. Results: The overall incidence of RM was 2.2%. Comparing with patients without RM, patients with RM tended to have a higher risk of deterioration, representing by higher ratio to be admitted to the intensiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Furthermore, rhabdomyolysis is a known cooccurrence [ 8 ] that might represent a contributing factor for adverse outcomes in some COVID-19 patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rhabdomyolysis is a known cooccurrence [ 8 ] that might represent a contributing factor for adverse outcomes in some COVID-19 patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is important to emphasize that there was no evidence of publication bias and that the overall effect size was not affected in sensitivity analyses. A number of unreported factors might have contributed to the heterogeneity, particularly the coexistence of rhabdomyolysis, reported in COVID-19 patients and a common cause of increased serum CK-MB concentrations [ [92] , [93] , [94] ], and the fact that virtually all selected studies reported a single measurement of CK-MB rather than serial assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, rhabdomyolysis with its symptoms such as fever, myalgia, and signs (elevated liver enzymes and lactate dehydrogenase) is similar to COVID-19 itself and may go unrecognized [ 22 ]. This is concerning as COVID-19 patients with concomitant rhabdomyolysis were found to have an increased risk of deterioration, increased risk of ICU admission (90.9% vs. 5.3%), increased mechanical ventilation (86.4% vs. 2.7%), and increased risk of in-hospital death [ 28 ]. Two independent risk factors for in-hospital deaths were creatine kinase (CK) levels greater than 1000 IU/L and serum myoglobin levels greater than 1000 ng/ml [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is concerning as COVID-19 patients with concomitant rhabdomyolysis were found to have an increased risk of deterioration, increased risk of ICU admission (90.9% vs. 5.3%), increased mechanical ventilation (86.4% vs. 2.7%), and increased risk of in-hospital death [ 28 ]. Two independent risk factors for in-hospital deaths were creatine kinase (CK) levels greater than 1000 IU/L and serum myoglobin levels greater than 1000 ng/ml [ 28 ]. However, Bach et al clarify that while both CK and myoglobin levels are monitored, Myoglobin levels are less useful in diagnosing rhabdomyolysis due to increased false-negative results, caused by myoglobin's short half-life [ 23 ].…”
Section: Introductionmentioning
confidence: 99%